PENGARUH PENGGUNAAN BAHAN AJAR MENGINTEGRASIKAN MATEMATIKA SAINS LAINNYA TEKNOLOGI BENCANA DAN KARAKTER (MSTBK) MENGGUNAKAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP PENCAPAIAN KOMPETENSI FISIKA SISWA KELAS X SMAN 7 PADANG - Yelvi Elia; Harman Amir (Universitas Negeri Padang, 2017)
Achievement of student physics competence in SMAN 7 Padang is still not maximal. The lack of competence is caused by several factors, these are the lack of student activeness during the lesson, less learning to apply the Physics concept, the limited availability of textbooks, the teaching materials used are not yet optimal in associating Physics with other knowledge and less varied methods. One solution to solve the problem is to apply teaching materials to integrate other Science Mathematics Disaster and Character Technology (MSTBK) by using Problem Based Learning (PBL) model in learning. The purpose of this research is to know the influence of teaching materials to integrate other Science Mathematics of Disaster and Character Technology (MSTBK) using Problem Based Learning (PBL) model to the achievement of Physics Competency of grade X SMAN 7 Padang students. The type of this research is a quasi experiment with Posttest-Only Control Group Design research design. The population of the study was students of class X MIA SMAN 7 Padang registered in academic year 2016/2017. The sample was taken by using purposive sampling technique. Analysis of the data for the knowledge competency test of equality of two average and split-plot analysis of variance (spanava) with graphs for competence attitudes and skills.Based on data analysis that has been done, got result for each student competence as follows: first, at attitude competence obtained fh = 2,41 and ft = 4,75 and skill competence obtained fh = 4,1 and ft = 7,17. This means that teaching materials integrating other Science Mathematics of Disaster and Character Technology (MSTBK) in the Problem Based Learning (PBL) model does not have a significant effect on students' attitude and skill competencies. Second, the knowledge competence obtained th = 2.12 and tt = 2.00. Based on the data analysis, it is found that there is a significant influence on the use of teaching materials to integrate other Science Mathematics of Disaster and Character Technology (MSTBK) in the Problem Based Learning (PBL) model to the achievement of Physics knowledge competency of grade X students SMAN 7 Padang